Exploring the Mechanism of 2ʹ-Hydroxychalcone Improving Copper Sulfate-Induced Inflammation in Zebrafish Through Network Pharmacology - Shen Y; Yao YD; Li H; Zhang Q; Wang CL; Hu L; Hu YC; Chen MH (Drug Design, Development and Therapy)
YuZhou Shen,1,* Yan Dong Yao,1,* Haili Li,1,* Qian Zhang,1,2,* Cheng Lin Wang,1,* Li Hu,1 Ying Chun Hu,1 Mu Hu Chen1 1Department of Emergency Medicine, The Affiliated Hospital of Southwest Medical University, Lu Zhou, People’s Republic of China; 2Department of Infectious Diseases Department, The Affiliated Hospital of Southwest Medical University, Lu Zhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Mu Hu Chen, Email cmh6186@swmu.edu.cn Ying Chun Hu, Email huyingchun913@swmu.edu.cnIntroduction: 2ʹ-Hydroxychalcone is universally acknowledged as a Chinese medicine monomer featured by aromatic properties, exhibiting anti-inflammatory and antioxidant effects. As a consequence, the study emphasis was placed on the anti-inflammatory, anti-oxidative and exercise capacity reinforcement effects of 2ʹ-Hydroxychalcone on Danio rerio young fish under the action of CuSO4. Simultaneously, research endeavors were made to delve into how functional changes of target affect the inflammation and exercise capacity of Danio rerio young fish.Methods: Upon mating breeding, mature transgenic zebrafish and type AB zebrafish expressing red fluorescent macrophages T g (mpeg1:m Cherry) were cultured for 72 h and exposed to 12.5, 6.25, 3.14 and 0uM 2ʹ-Hydroxychalcone, respectively, for three hours of pretreatment, which were subsequently incubated in CuSO4 at 20uM concentration for 12 h. A diverse array of test indexes was hereby utilized, encompassing the migration of red fluorescent-labeled macrophages, levels of inflammatory cytokines, zebrafish behavioral motility, and gene expression patterns correlated with oxidative stress and mitochondrial biogenesis, to assess the drugs’ efficacy in alleviating inflammation.Results: 2ʹ-Hydroxychalcone anti-inflammatory target protein was found by adopting the bioinformatics method. Its effect on zebrafish behavior ability and the change trend of oxidative stress index were explored by changing the functional state of the target, such as changing the functional activity of the target by micro-injection technology. As indicated by the results, 2ʹ-Hydroxychalcone could hinder the migration of macrophages and the mitochondrial function of CuSO4. Apart from that, 2ʹ-Hydroxychalcone could lessen the level of inflammatory factors and oxidative stress. In addition, 2ʹ-Hydroxychalcone conspicuously hindered the expression of interleukin-1β and interleukin-TNF-α, and lowered the expression of COX2. An augment in the levels of the target protein TRPV1 was observed during inflammation.Discussion: The experimental findings validated the anti-inflammatory and anti-oxidant activities of 2ʹ-Hydroxychalcone and preliminarily confirmed the effect of the target on the behavior and oxidative stress level of zebrafish.Keywords: 2ʹ-hydroxychalcone, CUSO4, mitochondrial biogenesis, oxidative stress reaction, behavior analysis system, ROS